Lack of Fc Gamma Receptor IIIA Promotes Rather than Suppresses Humoral and Cellular Immune Responses after Mucosal or Parenteral Immunization with Antigen and Adjuvants. (April 2017) - Sun, J.‐B.; Holmgren, J.; Cragg, M. S.; Xiang, Z.
Abstract: The Fcγ receptor IIIA (FcγRIIIA) has traditionally been known as a positive regulator of immune responses. Consistent with this, mice deficient in FcγRIIIA are protected from various inflammation‐associated pathologies including several autoimmune diseases. In contrast to this accepted dogma, we show here that mice lacking FcγRIIIA developed increased rather than reduced both humoral and cellular immune responses to mucosal (sublingual) immunization with ovalbumin (OVA) given together with the strong mucosal adjuvant cholera toxin as well as to parenteral (subcutaneous) immunization with OVA in complete Freund's adjuvant. After either route of immunization, in comparison with concomitantly immunized wild‐type mice, FcγRIIIA −/− mice had increased serum anti‐OVA IgG (IgG1 but not IgG2) antibody responses as well as augmented cellular responses that included memory B cells and effector T cells. The increments in immune responses in FcγRIIIA −/− mice were similar to those seen in FcγRIIB −/− mice. Furthermore, OVA‐pulsed FcγRIIIA −/− DCs, similar to OVA‐specific FcγRIIB −/− DCs, had enhanced capacity to activate OVA‐specific OT‐II T cells, which was even further pronounced when DCs were pulsed with IgG1‐complexed OVA. Our data support an inhibitory–regulatory role of FcγRIIIA on vaccine/adjuvant‐induced immune responses and demonstrate that lack of FcγRIIIA can promote rather than suppress both humoral and cellular immune responses.